Nursing Care For Heart Failure with Nursing Intervention in The Form of Heart Diet Education For Chf Patients at Menggala Regional General Hospital - Sugiarto; Winda Afikirtiani; Rengga Saputra (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2026)
Backround and objective: Patients with congestive heart failure (CHF) generally experience shortness of breath, which can cause a decrease in blood flow throughout the body. CHF patients can be treated by increasing contractility or systemic blood flow, providing rest time for patients, placing them in a semi-Fowler position, providing oxygen therapy as needed, reducing fluid and salt intake, and recording fluid balance. The subjects of this study were two patients who received treatment with a diagnosis of congestive heart failure (CHF) and experienced problems with decreased cardiac output. The complaint that occurred in both patients was shortness of breath due to impaired cardiac contractility, which caused lower cardiac output, resulting in decreased blood flow throughout the body. The objective of this study was to determine the effectiveness of applying cardiac diet nursing interventions in CHF patients undergoing treatment. Result: The results of the assessment of two patients with CHF who were given nursing care with health education about a low-salt diet and collaborative therapy administration. Conclusion: CHF patients can be treated by identifying the primary signs and symptoms of decreased cardiac output, monitoring TTV, monitoring fluid balance, and providing nursing care with health education about a low-salt diet and collaborative therapy administration.